Cross Country Study of Human Capital Formation and USFDI Inflows: Do Institutions Matter? - Bhattacharya, Barnana; Sinha, Chaitali (Finance & Economics Review, 2024)
Purpose: The neo-classical theory of economic growth features the positive impact of the human capital of an economy on its growth. The inflow of foreign direct investment is one of the main components to carry forward the growth effect, this study investigates the impact of country-specific institutional quality and human capital on the cross-country variations of US-Foreign Direct Investment (FDI) inflows. Our core hypothesis is that Countries with better Human capital will attract more FDI if they have good quality institutions in terms of less risk in investment opportunities. Method: Using a set of panel data of US-Foreign Direct Investment (FDI) inflows for both developed and developing countries over the period 1984-2021. Result: The country-specific quality of institutions reinforces the impact of human capital on the inflow of US foreign direct investment in this study. Using two-dimensional panel data we find strong support for our hypothesis using a two-way fixed effects model. Our results are robust to the alternative measures of institutional quality. Implications: The strength of our approach is that in contrast to the previous works (1) we have used the USFDI inflow across countries that have been widely neglected in the related literature and (2) emphasis has been given to the conditional or joint impact of human capital and country-specific institutional quality in determining the cross-country variations in USFDI inflows.